The Implementation Of Agile Methods In Designing A Web-Based Information System In The Geomin Laboratory Of Pt Antam Tbk - Dennis Bramastha; Waeisul Bismi (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2026)
The management of human resource administration at the Geomin Laboratory Unit of PT Antam Tbk, which includes recording attendance, overtime requests, and leave requests, faces various obstacles due to the continued implementation of manual procedures. This process, which relies on physical forms, is not only time-consuming in recapitulation, but is also prone to recording errors and document loss, as well as the lack of accurate quota monitoring. This study aims to design and build a web-based information system that can overcome these problems by integrating all administrative processes into a single digital platform. The development method used in this study is the Agile method, which allows for a flexible and iterative development process. This system is built using the Laravel framework and utilizes geolocation technology for attendance validation. The result of this study is a functional information system with key features such as dare attendance, a multi-level approval flow, and real-time leave quota management. Based on the results of the User Acceptance Test involving 15 respondents from various roles, this system achieved an acceptance rate of 93.1%, which falls into the “Highly Acceptable” category.